DINAMIKA KEBERDAYAAN MASYARAKAT DI SEKITAR PERTAMBANGAN DI KABUPATEN BOMBANA SULAWESI TENGGARA - Syafruddin, Syafruddin; Sumardjo, Sumardjo; Tjitropranoto, Prabowo; Fatchiya, Anna (Puslitbangkesos Kementerian Sosial RI, 2019)
The high poverty rate in Kabupaten Bombana showed the powerlessness of the community to improve their welfare, especially the communities around mining. This research aimed to: (1) analyze the dynamics of empowerment of communities around mining in Bombana District; (2) analyze the factors that influence the dynamics of empowerment of communities around mining in Bombana District. Research used survey methods. Samples were determined by proportional cluster random sampling. Data analysis was carried out descriptively and inferentially. Inferential statistical tests used SEM. The results of the study showed that the dynamics of community empowerment around mining in Bombana District as a whole were low category. The factors that influence the low dynamics of community empowerment were (1) Weak internal factors: low level of education, low motivation, number of family dependents, poor perception of mining and poor perceptions of empowerment by companies, and low levels of participation. (2) The low level of support from external factors: extension support, institutional support, social environment support, and communication support. (3) High social conflict: natural resource occupation process, company domination over natural resources, and handling negative impacts. (4) The low role of government and companies in empowerment programs. (5) Low of community adaptive competency. Keywords: dinamics, empowerment, community, mining